PENILAIAN MANAJEMEN KESISWAAN PADA MADRASAH TSANAWIYAH NEGERI KABUPATEN ACEH BESAR - Fadhilah Fadhilah; Arisnaini Arisnaini (ITB AAS Indonesia Surakarta, 2023)
The application of the student to the institution management is one of the necessity to improve the quality of education. Lack of school facilities and infrastructure become a major obstacle in the effective management of student affairs. This study aims to determine the planning implementation, monitoring, and evaluation of student management program. The method used in this research is descriptive qualitative approach. Techniques of data collection : observation, interview and documentation. Subjects were principals, teachers and students MTsN Cot Gue. The results showed that : student management plan prepared by the principal with the deputy head of the student and deputy head of the curriculum includes courses Admission, the capacity of new students, and new student se lection process, analyze subjects, draw up an annual program, the semester program, syllabus and Learning Program Plan. All the planning is composed arranged and documented. Implementation tailored to the student management plan that is prepared, either in relation to new admissions and student activities. Supervision of student management based on the management system, which is seeking any activities that have been planned, implemented and good supervision. Principals and teachers to supervise the implementation of student management. Both principals and teachers implement the roles and responsibilities based on the duties and functions for the management of student success.